Hypervelocity stars in the Gaia era Revisiting the most extreme stars from the MMT HVS survey - Kreuzer, Simon; Irrgang, Andreas; Heber, Ulrich (Astronomy & Astrophysics, 2020)
The hypervelocity star (HVS) survey conducted at the Multiple Mirror Telescope (MMT) identified 42 B-type stars in the Galactic halo whose radial velocity in the Galactic rest-frame exceeds +275 km s 1. In order to unravel the nature and origin of those highvelocity outliers, their complete six-dimensional phase space information is needed. To this end, we complemented positions and proper motions from the second data release of Gaia with revised radial velocities and spectrophotometric distances that are based on a reanalysis of the available MMT spectra of 40 objects using state-of-the-art model spectra and a tailored analysis strategy. The resulting position and velocity vectors for 37 stars were then used as input for a subsequent kinematic investigation to obtain as complete a picture as possible. The combination of projected rotational velocity, position in the Kiel diagram, and kinematic properties suggests that all objects in the sample except two (B576, B598) are very likely to be main sequence stars. While the available data are still not precise enough to constrain the place of origin for 19 program stars, we identified eight objects that either come from the outer rim of the Galactic disk or not from the disk at all, along with ten that presumably stem from the Galactic disk. For almost all of those 18 targets with more or less well-constrained spatial origin, the Galactic center (GC) is disqualified as a possible place of origin. The most notable exception is B576, the origin of which coincides extremely well with the GC when assuming a blue horizontal branch nature for it. HVS 22 is by far the most extreme object in the sample. Although its origin is completely unconstrained, an ejection from the GC by the Hills mechanism is the most plausible explanation for its current Galactic rest-frame velocity of 1530(-560)(+690) km s(-1).
Keywords: stars: distances; stars: early-type; stars: fundamental parameters; stars: kinematics and dynamics